2017
DOI: 10.1103/physrevd.95.094012
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic corrections to the form factors of Bc into S -wave charmonium

Abstract: We investigate the form factors of Bc meson into S-wave charmonium within the nonrelativistic QCD effective theory and obtain the next-to-leading order relativistic corrections to the form factors, where both the Bc meson and the charmonium are treated as the nonrelativistic bound states. Treating the charm quark as a light quark in the limit mc/m b → 0, some form factors are identical at the maximum recoil point, which are consistent with the predictions in the heavy-quark effective theory and the large-energ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 57 publications
(80 reference statements)
1
22
0
Order By: Relevance
“…For the B c → J/ψ form factors, they have been studied in a variety of approaches [106][107][108][109][110][111][112][113][114][115][116] (for earlier analysis focused on this decay mode see refs. [116][117][118][119]).…”
Section: Form Factorsmentioning
confidence: 99%
“…For the B c → J/ψ form factors, they have been studied in a variety of approaches [106][107][108][109][110][111][112][113][114][115][116] (for earlier analysis focused on this decay mode see refs. [116][117][118][119]).…”
Section: Form Factorsmentioning
confidence: 99%
“…For example, recently, the authors of ref. [1] have calculated the relativistic corrections to the form factors of the B c decays to S-wave charmonium by non-relativistic QCD (NRQCD) approach, with the heavy quark relative velocities v 2 J/ψ = 0.267 and v 2 Bc = 0.186. They pointed out that the relativistic corrections can bring about additional 15 ∼ 27% contributions.…”
Section: Introductionmentioning
confidence: 99%
“…The LHCb experiment can produce and reconstruct a large number of the B c meson events, and it provides a solid platform to study the properties of the B c meson precisely. A great deal of work has been done on various B c decays under different approaches, such as NRQCD approach [1,[11][12][13], the perturbative QCD approach (PQCD) [14][15][16][17], the relativistic quark model (RQM) [18][19][20][21], Light-cone sum rules (LCSR) [22], the nonrelativistic constituent quark model (NCQM) [23] and QCD sum rules (QCDSR) [24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile the NRQCD factorization has been adopted in refs. [18][19][20][21][22][23][24][25][26], in which the non-perturbative physics reside in a few NRQCD matrix elements. The LHCb collaboration has started comprehensive experimental studies of the decays [27], and some phenomenological studies can be found in refs.…”
Section: Jhep12(2017)012mentioning
confidence: 99%